Adsorvente de micotoxinas em dietas de frangos de corte contendo aflatoxina e fumonisina - Sobrane Filho, Sérgio Turra [UNESP] (2014)
The present study aimed to evaluate the effect of aflatoxin and fumonisin contamination and efficiency of the use of different levels of adsorbent -based on sodium calcium aluminiossilicate (SCAS) in minimizing the damage caused by the observation data of growth performance, hematological and biochemical parameters. 1440 broilers from Cobb® lineage have been used, from 22 to 42 days of age, in 48 plots in a completely randomized design with six treatments and eight repetitions of thirty birds each. The treatments were CP (positive control)-without mycotoxin and adsorbent; CP+0.30A-without mycotoxins and with adsorbent (0.30%); CN (negative control) - only mycotoxins (2 mg/kg AFB1 and 100 mg/kg FB1); CN+0.10A- with adsorbent (0.10%) and mycotoxins; CN+0.20A- with adsorbent (0.20%) and mycotoxin; CN+0.30A- with adsorvent (0.30%) and mycotoxins. At 42 days of age two birds per experimental plot were subjected to collection for hematological (hematocrit and count total and differential leukocytes) and at 43 days of age two birds per plot were subjected to collection for biochemical analysis (calcium , phosphorus , urea, creatinine , uric acid, cholesterol , triglycerides and gamma glutamyltransferase-GGT). The amount of AFB1 and the FB1 treatment CN affects the performance of the animal by reducing body weight gain (35%) and feed intake (50%) when compared to CP treatment and the treatments with SCAS levels of 0.20 and 0.30% inclusion (CN+0,20A and CN+0,30A) reducing losses. The birds of CN showed anemia and immunosuppression provided by mycotoxins and this situation was solved with the addition of SCAS levels of 0.20 and 0.30. Studying the hepatic system of birds of CN through biochemical analyzes of cholesterol and GGT, observed reduction in cholesterol and an increase in GGT were observed in relation to the CP , showing a picture of liver injury and difficulty in cholesterol synthesis , being ...